Startup, heat transfer, and flow characteristics of a ⊥-shaped oscillating heat pipe for application in a hybrid battery thermal management system - Lu, Hongkun; Muhamad, Mat Noor; Kadirgama, Kumaran; Beg, M. S. (Elsevier Ltd, 2025)
This study proposes a novel hybrid battery thermal management system (BTMS) combining an oscillating heat pipe (OHP) and liquid cooling plate to improve heat dissipation and temperature uniformity in battery packs. The key innovation is the use of a ⊥-shaped OHP with vertically aligned evaporator and condenser sections, offering dual heat transfer pathways. Experimental investigations were conducted to evaluate the startup, heat transfer, and flow characteristics of the ⊥-shaped OHP and its performance within the hybrid BTMS. Results showed that the ⊥-shaped OHP is more sensitive to the filling ratio than conventional OHP, with an optimal filling ratio of 26.1 % enabling reliable startup at low heat loads. At high heat loads, frequent transitions between slug and annular flows in the ⊥-shaped OHP enhanced heat transfer. Reducing coolant flow improved the startup performance of ⊥-shaped OHP under low heat loads, while increased flow rates had limited impact on heat transfer capability. Lower coolant temperatures decreased the startup temperature, and higher temperatures during stable operation reduced thermal resistance. Under a heat load of 280 W, the hybrid BTMS reduced the battery pack’s average surface temperature by 2.6 ◦C and the maximum temperature difference by 21.7 %, outperforming conventional liquid cooling systems. These findings suggest the hybrid BTMS is highly effective for high-load applications, offering improved temperature control and system stability